Adoptive transfer of dendritic cells expressing CD11c reduces the immunological response associated with experimental colitis in BALB/c mice - Paiatto, Lisiery N. [UNESP]; Silva, Fernanda G. D.; Yamada, Áureo T.; Tamashiro, Wirla M. S. C.; Simioni, Patricia U. [UNESP] (Public Library of Science (PLoS), 2018)
Introduction In addition to conventional therapies, several new strategies have been proposed for modulating autoimmune diseases, including the adoptive transfer of immunological cells. In this context, dendritic cells (DCs) appear to be one of the most promising treatments for autoimmune disorders. The present study aimed to evaluate the effects of adoptive transfer of DCs obtained from both naïve and ovalbumin (OVA)-tolerant mice on the severity of TNBS induced colitis and analyze the eventual protective mechanisms. Methods and results To induce oral tolerance, BALB/c mice were fed 4mg/mL OVA solution for seven consecutive days. Spleen DCs were isolated from tolerant (tDC) and naïve (nDC) mice, and then adop-tively transferred to syngeneic mice. Three days later, colitis was induced in DC treated mice by intrarectal instillation of 100μg2,4,6-trinitrobenzenesulfonic acid (TNBS) dissolved in 50% ethanol. Control subjects received only intrarectal instillation of either TNBS solution or a vehicle. Five days later, mice from all groups were euthanized and examined for physiological and immunological parameters. Regarding the phenotype, we observed that the frequencies of CD11+ MHC II+ and CD11+ MHCII+ CD86+ cells were significantly lower in DCs isolated from tolerant mice than in those from naive mice. However, pretreatment with both types of DCs was able to significantly reduce clinical signs of colitis such as diarrhea, rectal prolapse, bleeding, and cachexia, although only treatment with tDCs was able to prevent weight loss from instillation of TNBS. In vitro proliferation of spleen cells from mice treated with either type of DCs was significantly lower than that observed in splenic cell cultures of naïve mice.